2015
DOI: 10.1180/minmag.2015.079.5.01
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal alteration of chevkinite-group minerals: products and mechanisms. Part 1. Hydration of chevkinite-(Ce)

Abstract: Samples from Russia and Scotland are used to examine the interaction of the REE-Ti silicate chevkinite-(Ce) with hydrothermal fluids. Altered zones in crystals are distinguished by using areas of low intensity on backscattered-electron images, low analytical totals, increasingly large departures from stoichiometry and, in some cases, the presence of micropores. Initial alteration of the chevkinite results in strong Ca enrichment. With increasing degrees of alteration, Ca abundances drop sharply, as do those o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 41 publications
(90 reference statements)
2
15
0
Order By: Relevance
“…It should be stressed that the sequence is seen as essentially continuous, as the mineral assemblages changed in response to changing fluid composition and temperature decrease. Jiang (2006), Vlach and Gualda (2007) and Bagiński et al (2015) to hydrothermal alteration. During that process, however, Nb tends to increase and the La/Ce ratio decreases, features not seen in the study samples.…”
Section: Sequence Of Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be stressed that the sequence is seen as essentially continuous, as the mineral assemblages changed in response to changing fluid composition and temperature decrease. Jiang (2006), Vlach and Gualda (2007) and Bagiński et al (2015) to hydrothermal alteration. During that process, however, Nb tends to increase and the La/Ce ratio decreases, features not seen in the study samples.…”
Section: Sequence Of Eventsmentioning
confidence: 99%
“…Recent studies of the hydrothermal alteration of the chevkinite group of minerals (CGM) have revealed a diversity of alteration products, dependent, inter alia, on the composition of the host rock, the composition of the hydrothermal fluids and the pressure and temperature at which the alteration proceeded (Jiang 2006;Vlach and Gualda 2007;Bagiński et al 2015;Macdonald et al 2015Macdonald et al a, b, 2016. The diversity has consequences for the mobilization or retention of rare-metals and the significance for the formation of rare-metal deposits.…”
Section: Introductionmentioning
confidence: 99%
“…Full details of the analytical conditions used are given in Baginśki et al (2015) and will not be repeated here.…”
Section: Geological Settingmentioning
confidence: 99%
“…In our studies of the low-temperature alteration of the CGM, we have divided alteration schemes into two types: (1) those which started with compositional modification of the CGM and the production of a zone of 'altered chevkinite'; and (2) those where formation of this zone was followed by the formation of a new mineral assemblage. In a companion paper, Baginśki et al (2015) described examples of type (1) alteration. Here we describe an example of type (2), where the CGM was initially altered by interaction with hydrothermal fluids, followed by crystallization of assemblages dominated by epidote-supergroup minerals.…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of allanite and chevkinite in the studied carbonatites dikes suggests that the composition of the magmas is an important control on the stability fields of these minerals, a fact that is supported by the presence of primary allanite in rocks formed by processes of mixing magmatic fluids and a later hydrothermal fluid. Bagiński et al [76] and Macdonald et al [77] documented the alteration of chevkinite-(Ce) to a phase strongly enriched in Ti and depleted in Si, REE and Fe compared to the unaltered phase. In contrast to studies chevkinite did not alter to a member of the epidote-group, possibly because REE + Y abundance in chevkinite (43-50 wt %) is almost twice that observed in allanite.…”
Section: Compositions Of Ree Minerals With Different Origins In Finlandmentioning
confidence: 99%